Maximizing Land Potential: A Highest and Best Use Analysis for Serviced Apartments in Bali - Limantoro, Nicholas Jonathan; Anastasia, Njo (Civil Engineering Dimension, 2025)
Bali, renowned as a global tourist destination, faces increasing demand for modern and flexible accommodations catering to both tourists and digital nomads. This study explores the development potential of a 1,000 m² plot in Sanur, Bali, into a serviced apartment using the Highest and Best Use (HBU) method. Legal, physical, financial, and market feasibility analyses proposed a layout with 45.1% apartment units, 54.9% supporting facilities, and 33.6% green spaces. A 12-year cash flow projection demonstrates financial viability, with an Internal Rate of Return (IRR) of 18.71%, a Net Present Value (NPV) of IDR 23.442 billion, and a discounted payback period of 11.39 years. This study shows that serviced apartments offer sustainable land use, aligning with market demand while delivering optimal economic returns. This development also supports Bali’s growth as a modern residential hub and reinforces its reputation as a dynamic global tourist destination.